A Satellite‐Detected Terrestrial Gamma Ray Flash Produced by a Cloud‐to‐Ground Lightning Leader. Issue 15 (7th August 2020) - Pu, Yunjiao; Cummer, Steven A.; Huang, Anjing; Briggs, Michael; Mailyan, Bagrat; Lesage, Stephen
Abstract: We report measurements of a terrestrial gamma ray flash (TGF) detected by the Fermi Gamma‐ray Burst Monitor that was produced during a negative cloud‐to‐ground (CG) lightning leader. This is the first report of a downward directed TGF occurring during a CG flash but detected by a space‐based instrument. The gamma ray photons are produced 3 ms preceding a return stroke (−146 kA) and are essentially simultaneous with an isolated low frequency radio pulse. Based on timing, the pulse is estimated to initiate at approximately 6 km altitude, and its polarity indicates downward moving negative charge, the opposite of regular satellite‐detected upward TGFs. A likely scenario is that the runaway electrons accelerate into the upper, positively charged end of the leader in a high field region, with the reverse positron beam generating upward gamma rays detectable from space. A search for similar waveform features indicates that this type of downward CG‐TGF may occur prior to 1% of high peak current CG strokes. Extrapolating gives a global rate of 5–10% of previously known TGFs and potentially a significant fraction of global TGFs. Key Points: A TGF detected by Fermi GBM occurred 3 ms before a −CG stroke during the descending negative leader, coincident with a 120 μs radio pulse The radio pulse polarity indicates that it is likely a downward TGF produced at 6 km altitude with a reverse positron beam detected by Fermi GBM This type of downward CG‐TGF may occur prior to 1% of high‐intensity CG strokes, constituting 5–10% of the previously known TGF population